Gus Iqdam's Interpretation of the Hadith about Loving Science and Ulama' at the Sabilu Taubah Assembly: Pemaknaan Gus Iqdam tentang Hadis Mencintai Ilmu dan Ulama di Majlis Sabilut Taubah - Musthofa, Qowim (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The great urgency in loving knowledge and the ulama' is truly felt by various groups of society, including Gus Iqdam, the caregiver of the Sabilu Taubah assembly. This assembly was attended by tens of thousands of people who went viral on social media, so anything that emerged from Gus Iqdam would attract the attention of the wider public. This article discusses Gus Iqdam's interpretation of the hadith of loving knowledge and ulama at the Sabilu Taubah assembly which was done very simply, thus raising the question; What is Gus Iqdam's method of explaining hadith regarding science and ulama?, and what are the implications for the congregation?. Furthermore, this research uses qualitative methods with descriptive delivery and uses a content analysis approach. As a result, there are two conclusions from the results of this study; Firstly, Hadith is used by Gus Iqdam as a motivational guide for the audience. Second, Gus Iqdam uses a simple normative-contextual paradigm and focuses on adjusting the psychology of the congregation so that the practical meaning of the hadith can be conveyed according to the conditions of the recipient.